Learning styles among high achievers / Nurhidayah Masni Abdullah … [et al.] - Abdullah, Nurhidayah Masni; Ahmad, Salimah; Omar, Zakiyah; Syed Wahid, Sharifah Norhuda (2011)
The process of teaching and learning will be more effective if teachers and learners know their potential, strength and weaknesses. The aim of this study is to identify the learning style among high academic achievers and students with average academic performance. Students with CGPA above 3.0 at UiTM Pahang are encouraged to join the high achievers club and they were selected as our respondents. An index of learning style questionnaires (ILS) developed by Felder and Solomon (2005) were distributed to the students from this club and selected students with average academic performance from science and social science faculties. The respondents' feedback were analyzed based on the four domains of learning styles which are active-reflective, sensing-intuitive, visual-verbal and sequential-global. The findings revealed that excellent students are more intuitive and more visual than students with average academic performance.